The Age, Sex, and Geographical Distribution of Self-Reported Asthma Triggers on Children With Asthma in China - Zhang, Changhao; Kong, Yan; Shen, Kunling (Frontiers in Pediatrics, 2021)
Background Asthma can be exacerbated by many triggers, and the heterogeneity of asthma triggers is clear among children with asthma. This study describes asthma triggers using a large-scale electronic dataset from the smartphone-based Chinese Children's Asthma Action Plan (CCAAP) app and aims to examine the difference in asthma triggers among different subgroups of children with asthma. Methods Data from the smartphone-based CCAAP app between February 22, 2017, and November 23, 2020, were reviewed, and children with asthma who reported their asthma triggers were enrolled. Eight common asthma triggers were listed in the software: upper respiratory infection, allergen sensitization, exercise, emotional disturbances, pungent odors, air pollution/smog, weather change, and tobacco smoke. We compared the incidence of asthma triggers among different subgroups (<6 years vs. 6-17 years; boy vs. girl; eastern region vs. central region vs. western region). Results We enrolled 6835 patients with self-reported asthma triggers. When compared by sex, boys had a higher proportion of exercise-triggered asthma than girls (boys vs. girls, 22.5% vs. 19.7%, P<0.05). The proportion of patients <6 years of age with upper respiratory infection (URI)-triggered asthma was higher than that of patients 6-17 years of age. Patients 6-17 years of age were more likely than patients <6 years of age to report five of the asthma triggers: allergen sensitization, exercise , pungent odors, air pollution/smog, and tobacco smoke. In subgroups based on geographical distribution, asthma triggering of allergen sensitization was reported to be the most common in patients from the eastern region (eastern region vs. central region vs. western region, 35.0% vs. 24.6% vs. 28.0%, P<0.001). Exercise-triggered asthma was found to be the most prevalent among patients from the central region (eastern region vs. central region vs. western region, 21.6% vs. 24.8% vs. 20.4%, P<0.05). However, the proportion of patients with air pollution/smog as an asthma trigger was the lowest among those from the western region. Conclusions Children with asthma present different types of asthma triggers, both allergenic and nonallergenic. Age, sex, and geographical distribution affect specific asthma triggers. Preventive measures can be implemented based on a patient’s specific asthma trigger.